ENF Based Robust Media Time-Stamping - Vatansever, Saffet; Dirik, Ahmet Emir; Memon, Nasir (Ieee-Inst Electrical Electronics Engineers Inc, 2022)
Electric Network Frequency (ENF) continuously fluctuates around a nominal value (50/60 Hz) due to a persistent imbalance between supplied and demanded power. In certain circumstances, ENF gets intrinsically embedded into audio and video recordings and can be extracted from these recordings. Consequently, ENF can be used in a number of media forensic applications, such as verifying the time of recording of the media. In this work, a robust media time-stamping approach is proposed for media whose ENF content is relatively contaminated. It essentially entails two procedures: first, detecting all useful, i.e., considerably accurate, samples of an estimated ENF signal, and then applying an adapted normalized cross-correlation process that is designed for exploiting just the selected ENF portions based on a binary mask of the identified accurate samples. Experimental results show that the proposed approach provides significantly increased performance.
Keywords: Media; Noise measurement; Forensics; Recording; Harmonic analysis; Estimation; Signal processing algorithms; ENF; electric network frequency; media forensics; multimedia forensics; time-of-recording; time-stamping